Knowledge management and alliance management capacity: A literature review from June to December 2021 - Gómez-Bayona, Ledy; García Gutiérrez, Sorely; Montes Gómez, Luis Fernando; Vélez Bernal, Olga (Cuadernos de Administración, 2023)
Individual and organizational knowledge has generated an important change in the development of business and institutional processes. Knowledge Management (KM) has played an important role in the development of new methodologies and the implementation of good corporate practices. The objective of this research is to describe the concepts of knowledge management and the capacity to manage alliances according to the scientific literature as well as the guidelines of the Ministry of Science, Technology, and Innovation. A literature review in the main scientific databases, such as Scopus, Redalyc, and SciELO, among others, is used as a methodology. Concluding that it is giving way to the ability to manage strategic alliances that talk about key factors that contribute to administrative models that promote the development of the intellectual capital of individuals and organizations, as well as these issues being of vital importance for the development of business knowledge management and making better use of the talents of individuals.